Danger Signals and Graft-versus-host Disease: Current Understanding and Future Perspectives - Toubai, Tomomi; Mathewson, Nathan D.; Magenau, John; Reddy, Pavan (Frontiers in Immunology, 2016)
Graft-versus-host response after allogeneic hematopoietic stem cell transplantation (allo-HCT) represents one of the most intense inflammatory responses observed in humans. Host conditioning facilitates engraftment of donor cells but the tissue injury causes from it primes the critical first steps in the development of acute graft-versus-host disease (GVHD). Tissue injuries release pro-inflammatory cytokines (such as TNF-α, IL-1β and IL-6) through widespread stimulation of pattern recognition receptors (PRRs) by the release of danger stimuli such as damage associated molecular patterns (DAMPs) and pathogen associated molecular patterns (PAMPs). DAMPs and PAMPs function as potent stimulators for host and donor derived antigen presenting cells (APCs) that in turn activate and amplify the responses of alloreactive donor T cells. Emerging data also point towards a role for suppression of DAMP induced inflammation by the APCs and donor T cells in mitigating GVHD severity. In this review, we summarize the current understanding on the role of danger stimuli such as the DAMPs and PAMPs in GVHD.